Possibilities of the action research - Natalia Zygmunt (Studia z Teorii Wychowania)
The aim of the article is to show the possibilities created by the use of the action research method in social research. The first part of the article presents a historical outline of action research and an overview of the ways of defining this method, as well as its different types, features and stages. The last part of the article presents the variety of research using a given method.